The Application Of A Discovery Learning Assisted By A Counting Board To Improve The Learning Outcomes Of Grade 1 Mathematics At SDN 02 Giriwondo - Nurjanah, Nurjanah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Based on the results of the author's observations of grade 1 students at SD N 02 Giriwondo, the results of 62% of students' scores are still below the KKM. From the results of observations during the learning process of mathematics on addition and subtraction as many as 8 students out of 13 students scored below the KKM, during learning 31% were active, 46% were less active and 23% were not active during the learning process, the researcher used a conventional learning model with the lecture method. The research conducted was a class action research. This research uses several data collection techniques including tests, observation, and documentation. Data collection was carried out through the stages of planning, action, observation, and reflection. The results showed that student learning outcomes increased as seen from the acquisition of average scores that met the Minimum Completion Criteria (KKM) standards, starting from the pre-cycle of 70 and in cycle 1 it increased to 75 while in cycle 2 it increased  to 81.